2020
DOI: 10.3390/ijerph17041363
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities of Polycyclic Aromatic Hydrocarbons for Aquatic Animals

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are organic compounds that are widely distributed in the air, water, and soil. Recently, the amount of PAHs derived from fuels and from incomplete combustion processes is increasing. In the aquatic environment, oil spills directly cause PAH pollution and affect marine organisms. Oil spills correlate very well with the major shipping routes. Furthermore, accidental oil spills can seriously impact the marine environment toxicologically. Here, we describe PAH toxicities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 387 publications
(158 citation statements)
references
References 187 publications
1
126
1
2
Order By: Relevance
“…The present highest values of NAP, ACE, ACEL, FLU, PHE, ANT, CAR, FLA, PYR, bANT, CHR, bbFLA, bkFLA, bPYR, dbANT, inPYR and bPRL in water; 1.41, 0.42, 1.80, 3.37, 2.95, 1.47, 0, 43.5, 42.3, 10.2, 9.89, 5.00, 1.96, 1.83, 2.36, 1.63, and 0.82 ng L -1 and their mean values 0.27, 0.03, 0.41, 0.48, 0.28, 0.11, 0, 5.24, 6.43, 19.06 ng L -1 for NAP, ACEL, ACE, FLU, ANT, PHE, FLU, PYR, bANT, CHR, bbFLU, bkFLU, bPYR, dbANT, bPRL and inPYR, respectively, in Suez Canal within Suez region [16]. The present total PAHs ND -114.00 ng L -1 were also remarkably lower than the reported values in Suez Canal (992.56 ng L -1 ) and Alexandria port (1364.59 ng L -1 ) but are still 10 times higher than that of the Sea of Japan [17].…”
Section: Assessment Of Polycyclic Aromatic Hydrocarbonmentioning
confidence: 62%
“…The present highest values of NAP, ACE, ACEL, FLU, PHE, ANT, CAR, FLA, PYR, bANT, CHR, bbFLA, bkFLA, bPYR, dbANT, inPYR and bPRL in water; 1.41, 0.42, 1.80, 3.37, 2.95, 1.47, 0, 43.5, 42.3, 10.2, 9.89, 5.00, 1.96, 1.83, 2.36, 1.63, and 0.82 ng L -1 and their mean values 0.27, 0.03, 0.41, 0.48, 0.28, 0.11, 0, 5.24, 6.43, 19.06 ng L -1 for NAP, ACEL, ACE, FLU, ANT, PHE, FLU, PYR, bANT, CHR, bbFLU, bkFLU, bPYR, dbANT, bPRL and inPYR, respectively, in Suez Canal within Suez region [16]. The present total PAHs ND -114.00 ng L -1 were also remarkably lower than the reported values in Suez Canal (992.56 ng L -1 ) and Alexandria port (1364.59 ng L -1 ) but are still 10 times higher than that of the Sea of Japan [17].…”
Section: Assessment Of Polycyclic Aromatic Hydrocarbonmentioning
confidence: 62%
“…Two to 3 rings PAHs show a greater solubility in water and a relatively slow metabolism, suggesting that the abundance of these compounds in the fish muscles is likely due to their uptake through the gills (Bautista et al 2019 ). Noteworthy, several studies have shown a negative correlation between the accumulation of PAHs in several species and their log K ow , which lead to a higher bioavailability of LMW-PAHs (Dsikowitzky et al 2016 ; Oliva et al 2017 ; Honda and Suzuki 2020 ). On the other hand, HMW-PAHs bind to the sediments and to organic colloidal particles.…”
Section: Resultsmentioning
confidence: 99%
“…PAH toxicity has been extensively studied. These compounds are well known for their carcinogenicity [ 28 , 29 ], mutagenicity [ 30 ], endocrine-disrupting activity [ 31 ], and developmental toxicity [ 32 , 33 ]. Owing to their toxicity and distribution, the United States Environmental Protection Agency has selected 16 representative PAHs as priority compounds for environmental monitoring.…”
Section: Introductionmentioning
confidence: 99%